Summary Documentation for the IRIS UMETRICS 2019 Data Release - Nicholls, Natsuko; Uberseder, Lindsay; Owen-Smith, Jason (Institute for Research on Innovation and Science (IRIS), 2019)
This is a publicly available summary of the full data documentation, providing project and data descriptions for the IRIS UMETRICS 2019 Data Release.